A Tale of Two Diseases: Parry Romberg Syndrome and En Coup De Sabre: A Case Report - Hasnain, Saqib; Erfan, Muhammad; Ahmed, Syed Afaq; khan, Ikram ullah; Hasnain, Saqib (International Journal of Pathology, 2018)
Background: Parry Romberg syndrome is a very rare disorder of unknown etiology. A degenerative acquireddisorder characterized by hemifacial atrophy. It can present with skeletal, dental and soft tissue abnormalitieswith or without CNS symptoms. Majority of the affected patients have manifestations of the disease in the firsttwo decades of life. Many cases have been documented having combination of Parry Romberg syndrome andanother form of localized scleroderma- en coup de sabre morphea. Histological features of the disease include fibrosiswith atrophy of adipose tissue and lack of any inflammatory infiltrate. Limited treatment options make thedisease difficult to manage.Case presentation: We present a case of an otherwise perfectly healthy, 12 years old girl with early features ofhemi-facial atrophy and en coup de sabre morphea.Conclusion: Both Parry Romberg syndrome and en coup de sabre morphea have many localized and systemicassociations. In many case reports neurological and dental abnormalities have been described. In our case patientdid not appear to have any of these.